2014
DOI: 10.1371/journal.pone.0093801
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Seven Chemical Pretreatments of Corn Straw for Improving Methane Yield by Anaerobic Digestion

Abstract: Agriculture straw is considered a renewable resource that has the potential to contribute greatly to bioenergy supplies. Chemical pretreatment prior to anaerobic digestion can increase the anaerobic digestibility of agriculture straw. The present study investigated the effects of seven chemical pretreatments on the composition and methane yield of corn straw to assess their effectiveness of digestibility. Four acid reagents (H2SO4, HCl, H2O2, and CH3COOH) at concentrations of 1%, 2%, 3%, and 4% (w/w) and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
108
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 38 publications
(49 reference statements)
13
108
2
Order By: Relevance
“…Because they are abundant in renewable biomass with low treatment costs, they are broadly employed for methane production in recent years [2]. Anaerobic digestion of lignocellulosic biomass for methane production is usually used for its simultaneous recovery of methane as a renewable energy source and residual solids or liquid as green fertilizers [3,4]. However, lignocellulose solubilization is the rate-limiting step for methane production during anaerobic digestion [5,6], and microorganisms with high efficiency of lignocellulose degradation are highly important for improving the performance of anaerobic digestion.…”
Section: Introductionmentioning
confidence: 99%
“…Because they are abundant in renewable biomass with low treatment costs, they are broadly employed for methane production in recent years [2]. Anaerobic digestion of lignocellulosic biomass for methane production is usually used for its simultaneous recovery of methane as a renewable energy source and residual solids or liquid as green fertilizers [3,4]. However, lignocellulose solubilization is the rate-limiting step for methane production during anaerobic digestion [5,6], and microorganisms with high efficiency of lignocellulose degradation are highly important for improving the performance of anaerobic digestion.…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al (2016) reported on the twofold methane yield increase as an effect of combined physical-chemical pretreatment (alkaline-hydrodynamic cavitation) of wheat straw basic material. Song et al (2014) investigated the effect of various acidic and alkaline pretreatments of wheat straw on the methane yield. According to their results, yield was improved from 100.6 ml/g VS (from untreated basic material) to 216.7 ml/g VS (optimum pretreated basic material).…”
Section: Introductionmentioning
confidence: 99%
“…Oji et al (2007) on the composition change of corn stalk after ammoniation pretreatment showed that ammoniation pretreatment could effectively increase the nitrogen content of corn stalk and reduce its cellulose and hemicellulose contents. Ammonia pretreatment significantly improved cumulative biogas yield, biogas production rate, and volatile solid (VS) reduction of straw (Song et al 2012;Li et al 2014).…”
Section: Introductionmentioning
confidence: 99%